Type O blood, the MCHC, and the reticulocyte count impact the early recurrence of primary warm-antibody autoimmune hemolytic anemia in children: A retrospective cohort analysis - Li, Jiacheng; An, Xizhou; Xu, Ximing; Xiao, Li; Wang, Yang; Zhu, Yao; Huang, Lan; Zhang, Kainan; Yao, Xinyuan; Yi, Weijia; Qin, Jiebin; Yu, Jie (Frontiers in Pediatrics, 2022)
Objective: Pediatric primary warm-antibody autoimmune hemolytic anemia (w-AIHA) are prone to recurrence. This study aims to identify the risk indicators for early recurrence of primary w-AIHA and to construct an effective recurrence risk assessment model. Methods: This study is a retrospective cohort study. The clinical data of primary w-AIHA patients hospitalized in the Department of Hematology and Oncology, Children's Hospital of Chongqing Medical University from January 1, 2018 to September 30, 2021 at the time of initial diagnosis were collected. Uni- and Multi-variate Logistic regression analysis were used to determine the risk indicators for early recurrence of primary w-AIHA in children, and ROC curve and Kaplan-Meier survival analysis were used to verify these indicators. Finally, a risk assessment model for early recurrence in children with primary w-AIHA was construct by Cox regression and visualized by nomogram. It was also verified by internal validation and external validation respectively. Results: 62 children with primary w-AIHA are included in the study, of which 18 recurred in 1 year after initial diagnosis. Uni- and Multi-variate Logistic regression showed that blood type O and reticulocyte count(Ret) were risk indicators for early recurrence of pediatric primary w-AIHA (P=0.009, 0.047, respectively). Mean corpuscular hemoglobin concentration (MCHC) was a protective factor (P=0.040). According to ROC curve analysis and Kaplan-Meier survival analysis, children with primary w-AIHA whose blood type was O, or MCHC<313.5pg/fL, or Ret≥0.161×1012/L had a higher risk of early recurrence (HR=2.640, 4.430 and 4.450respectively, and P=0.040, 0.015 and 0.018 respectively). The blood type O, MCHC and Ret of 56 patients were inserted into the Cox regression model, the recurrence risk assessment model for children with primary w-AIHA was successfully constructed and visualized by Nomogram. And the calibration curves and decision-curve analysis (DCA) curve suggested that the risk model had certain clinical applicability and effectiveness. Conclusions: Children with Blood type O, or MCHC<313.5pg/fL or Ret≥0.161×1012/L have higher risk in early recurrence of primary w-AIHA. The risk assessment model for early recurrence of pediatric primary w-AIHA established in this study has good clinical applicability and effectiveness.